Frequency of Bundle Branch Blocks in Patients with Coronary Syndrome and Its Relationship with Coronary Angiography and Mace Within 30 Days - Hamayon, .; Ahmad, Sajjad; Butt, Mukarram Mahmood; Javeed, Muhammad; Ullah, Zakir; Taha, Muhammad (Biological and Clinical Sciences Research Journal, 2025)
Bundle Branch Blocks (BBBs) are electrical conduction abnormalities in the heart that occur when there is a delay or interruption in the electrical impulse traveling through the right or left bundle branches. Objective: The study’s main objective is to determine the frequency of bundle branch blocks in patients with acute coronary syndrome. Methods: This prospective observational study was conducted at the Department of Cardiology, Punjab Institute of Cardiology, Lahore during June to December 2024.One hundred patients fulfilling the selection criteria were enrolled in the study from the emergency department. Informed consent was obtained from patients. Results: Data were collected from 100 patients, with a mean age of 55.23 ± 3.45 years, with 70% male and 30% female. Key risk factors included smoking history (>5 pack-years) in 45% of patients, alcohol consumption (>20 ml/day) in 15%, hypertension in 55%, diabetes in 40%, dyslipidemia in 50%, and a family history of ACS in 35%. Regarding the types of ACS, STEMI was observed in 60% of patients, NSTEMI in 30%, and unstable angina in 10%, highlighting STEMI as the predominant clinical presentation. The electrocardiographic analysis revealed that 14% of patients presented with right bundle branch block (RBBB) and 5% with left bundle branch block (LBBB). Conclusion: It is concluded that bundle branch blocks (BBBs), particularly right bundle branch block (RBBB), are significant markers of severe coronary artery disease and adverse outcomes in acute coronary syndrome (ACS) patients.